Synergistic function of four novel thermostable glycoside hydrolases from a long-term enriched thermophilic methanogenic digester - Wang, Meng; Lai, Guo-Li; Nie, Yong; Geng, Shuang; Liu, Liming; Zhu, Baoli; Shi, Zhongping; Wu, Xiao-Lei (Frontiers in Microbiology, 2015)
In biofuel production from lignocellulose, low thermostability and product inhibition strongly restrict the enzyme activities and production process. Application of multiple thermostable glycoside hydrolases, forming an enzyme “cocktail”, can result in a synergistic action and therefore improve production efficiency and reduce operational costs. Therefore, increasing enzyme thermostabilities and compatibility are important for the biofuel industry. In this study, we reported the screening, cloning and biochemical characterization of four novel thermostable lignocellulose hydrolases from a metagenomic library of a long-term dry thermophilic methanogenic digester community, which were highly compatible with optimal conditions and specific activities. The optimal temperatures of the four enzymes, β-xylosidase, xylanase, β-glucosidase, and cellulase ranged from 60°C to 75°C, and over 80% residual activities were observed after 2 h incubation at 50°C. Mixtures of these hydrolases retained high residual synergistic activities after incubation with cellulose, xylan, and steam-exploded corncob at 50°C for 72 h. In addition, about 55% dry weight of steam-exploded corncob was hydrolyzed to glucose and xylose by the synergistic action of the four enzymes at 50°C for 48 h. This work suggested that since different enzymes from a same ecosystem could be more compatible, screening enzymes from a long-term enriching community could be a favorable strategy.